Liver tissue changes during and post 6-month spaceflight as measured by ultrasound radio frequency signal processing - Arbeille, Philippe; Zuj, Kathryn; Guillon, Laurent (Frontiers in Physiology, 2024)
Background Analysis of ultrasound radio frequency (RF) signals allows for the determination of the index of reflectivity (IR), which is a new measure that is dependent on tissue properties. Previous work has shown differences in the IR of the carotid artery wall with long-duration spaceflight; therefore, it was hypothesized that liver tissue would also show differences in this measure with spaceflight. Methods The RF signal of a liver tissue region of interest (ROI) was displayed and processed along six different lines covering a surface of approximately 2 cm × 2 cm. The IR was calculated as the energy backscattered by the liver ROI divided by the total energy returned to the ultrasound probe. Results Seven astronauts were investigated preflight, inflight on day 150, and postflight 4 days and 6 months after rerunning to Earth. Compared to preflight (63% ± 18%), the liver tissue ROI IR was significantly lower on flight day 150 (46% ± 14%; p = 0.027) and 4 days postflight (46% ± 19%; p = 0.025). At 6 months postflight, the IR returned to preflight values (59% ± 13%; p = 0.919). Conclusion The significant decrease in the coefficient of reflectivity inflight and 4 days postflight indicates an alteration in the liver tissue that reduces the reflection of ultrasound waves. This change in tissue properties could either be due to the addition of particles that do not reflect ultrasound waves or structural or cellular changes that alter the reflectivity of the tissue.